2014
DOI: 10.1371/journal.pone.0107403
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Assessment of Bioengineered Bone in a Muscle Flap for the Reconstruction of Critical-Size Mandibular Defect

Abstract: This study presents a comprehensive radiographic evaluation of bone regeneration within a pedicled muscle flap for the reconstruction of critical size mandibular defect. The surgical defect (20 mm×15 mm) was created in the mandible of ten experimental rabbits. The masseter muscle was adapted to fill the surgical defect, a combination of calcium sulphate/hydroxyapatite cement (CERAMENT™ |SPINE SUPPORT), BMP-7 and rabbit mesenchymal stromal cells (rMSCs) was injected inside the muscle tissue. Radiographic assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The aim of the clinical case reports and ex vivo experiments was to target the use of the skeletal muscles as a bioreactor. These case studies have been discussed [ 15 , 16 , 18 20 ] in vivo experiments. For these reasons, most of the case studies have suggested the use of the skeletal muscles as a biomimetic supporting scaffold in order to facilitate the bone formation process, which also provides the much-needed vascularity.…”
Section: Literature-reported Methods Of Avoiding Ischemia–reperfusion...mentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of the clinical case reports and ex vivo experiments was to target the use of the skeletal muscles as a bioreactor. These case studies have been discussed [ 15 , 16 , 18 20 ] in vivo experiments. For these reasons, most of the case studies have suggested the use of the skeletal muscles as a biomimetic supporting scaffold in order to facilitate the bone formation process, which also provides the much-needed vascularity.…”
Section: Literature-reported Methods Of Avoiding Ischemia–reperfusion...mentioning
confidence: 99%
“…Further clinical experimentations suggest the use of In vivo osteogenic properties for the grafting of skeletal muscles. Such experimentation shows that novel strategies can be implemented to facilitate effective bone regeneration [ 19 , 20 , 23 ]. For example, more recently, it has been established that decellularized skeletal muscles (Fig.…”
Section: Literature-reported Methods Of Avoiding Ischemia–reperfusion...mentioning
confidence: 99%
“…Pre-clinical protocols associate cells with various biomaterials and biomolecules essential for a good differentiation performance. Gene transfer is used as a tool to stimulate and accelerate the process of tissue specialization (155,156). Clinical trials, on the other hand, are still in early stages and focus on cells with safer and less bold associations such as fibrin glue.…”
Section: Tissue Engineeringmentioning
confidence: 99%